Manipulation of Electrostatic and Saccharide Linker Interactions in the Design of Efficient Glycopolypeptide-Based Cholera Toxin Inhibitors - Maheshwari, Ronak (2010)
[Image: see text] Multivalent, glycopolymer inhibitors designed for the treatment of disease and pathogen infection have shown improvements in binding correlated with general changes in glycopolymer architecture and composition. We have previously demonstrated that control of glycopolypeptide backbone extension and ligand spacing significantly impacts the inhibition of the cholera toxin B subunit pentamer (CT B(5)) by these polymers. In the studies reported here, we elucidate the role of backbone charge and linker length in modulating the inhibition event. Peptides of the sequence AXPXG (where X is a positive, neutral or negative amino acid), equipped with the alkyne functionality of propargyl glycine, were designed and synthesized via solid-phase peptide synthetic methods and glycosylated via Cu(I)-catalyzed alkyne-azide cycloaddition reactions. The capacity of the glycopeptides to inhibit the binding of the B(5) subunit of cholera toxin was evaluated. These studies indicated that glycopeptides with a negatively charged backbone show improved inhibition of the binding event relative to the other glycopeptides. In addition, variations in the length of the linker between the peptide and the saccharide ligand also affected the inhibition of CT by the glycopeptides. Our findings suggest that, apart from appropriate saccharide spacing and polypeptide chain extension, saccharide linker conformation and the systematic placement of charges on the polypeptide backbone are also significant variables that can be tuned to improve the inhibitory potencies of glycopolypeptide-based multivalent inhibitors.